Platelet levels and age are determinants of survival after mild–moderate TBI: A prospective study in Spain - Yuguero, Oriol; Vena, Ana; Bernal, Maria; Martínez-Alonso, Montserrat; Farre, Joan; Purroy, Francisco (Frontiers in Public Health, 2023)
Introduction Traumatic brain injury (TBI) is a very important reason for consultation in Emergency Departments. Methods A hospital cohort study with patients who attended the Hospital Emergency Department between June 1, 2018 and December 31, 2020 due to TBI. Clinical and sociodemographic variables were recorded. Also, levels of biomarkers and management variables were used. Survival analyses were performed by fitting a multivariable Cox regression model for patient survival during the follow-up of the study in relation to the patient’s characteristics upon admission to the emergency room. Results 540 patients were included. The mean age was 83 years, with 53.9% of male patients. 112 patients (20.7%) died during study follow-up. The mortality rate per 100 person-years was 14.33 (11.8-17.24), with the most frequent mechanism being falls in the home and none on public roads. The multivariable Cox proportional hazards model showed that survival after TBI was significantly associated with age, S100 levels, Charlson Index, patient's institutionalized status, place where the TBI occurred, and hemoglobin and platelet levels. Discussion The most common profile for suffering a TBI was being male and aged between 80 and90 years. The combination of the variables age, Charlson index, place of TBI occurrence and hemoglobin and platelet levels could offer early prediction of survival in our population independently of TBI severity. With the data obtained, a therapeutic algorithm could be established for patients suffering from mild TBI, allowing the patient to be supervised at home, avoiding futile referrals to the emergency services.